The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.15625/2615-9783/15925
|View full text |Cite
|
Sign up to set email alerts
|

NDSHA - The New Paradigm for RSHA - An Updated Review

Abstract: A New Paradigm (data driven and not like the currently model driven) is needed for Reliable Seismic Hazard Assessment RSHA. Neo-Deterministic Seismic Hazard Assessment (NDSHA) integrates earthquake geology, earthquake science, and particularly earthquake physics to finally achieve a New (and needed) Paradigm for Reliable Seismic Hazard Assessment RSHA.Although observations from many recent destructive earthquakes have all confirmed the validity of NDSHA’s approach and application to earthquake hazard forecasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 138 publications
(196 reference statements)
0
10
0
Order By: Relevance
“…The history and detailed technical description of NDSHA has been reviewed in several publications, e.g., [32,43,44,51,53,54]. The Neo-deterministic Seismic Hazard Assessment (NDSHA) originated in 1996 [55], and was seen as a response to several drawbacks of Probabilistic Seismic Hazard Analysis (PSHA) widely used in the world [49].…”
Section: Ndsha Approach: Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The history and detailed technical description of NDSHA has been reviewed in several publications, e.g., [32,43,44,51,53,54]. The Neo-deterministic Seismic Hazard Assessment (NDSHA) originated in 1996 [55], and was seen as a response to several drawbacks of Probabilistic Seismic Hazard Analysis (PSHA) widely used in the world [49].…”
Section: Ndsha Approach: Methodologymentioning
confidence: 99%
“…Different from standard PSHA and classical DSHA [56], NDSHA does not rely on the use of empirical attenuation relations and a limited set of scenario earthquakes, but starts from basic physics and takes into consideration the mechanical properties of earthquake sources and pathways to compute realistic synthetic seismograms and to depict the hazard level at the sites of interest (e.g., [32]). Since 1996, the neo-deterministic approach has undergone several rehearsals and improvements (e.g., [32,43,44,51,53,57,58]). It has been developed as a comprehensive multi-disciplinary approach for performing multi scenario-based seismic hazard computations based on all available geophysical-geological-tectonic information, and could be applied from national to local scale [33].…”
Section: Ndsha Approach: Methodologymentioning
confidence: 99%
“…The Neo-Deterministic Seismic Hazard Assessment (NDSHA) methodology (Fäh et al, 1993;Panza et al, 2012;Peresan et al, 2012a;Bela and Panza, 2021;Panza and Bela, 2020 and references therein) has demonstrated its abilities to serve as the Standard Method for Reliable Seismic Hazard Assessment (RSHA). NDSHA, proposed some 20 years ago (Panza et al, 1996;, has proven to both reliably and realistically simulate comprehensive sets of hazardous earthquake ground motions throughout many regions worldwide.…”
Section: Seismic Roulette Is a Game Of Chancementioning
confidence: 99%
“…The NDSHA methodology (Bela & Panza, 2021;Fäh et al, 1993;Panza et al, 2012;Panza & Bela, 2020;Peresan et al, 2012) demonstrates its ability to serve as the standard method for Reliable Seismic Hazard Assessment (RSHA). NDSHA method, proposed some 20 years ago (Panza et al, 1996;, has proven to both reliably and realistically simulate comprehensive sets of hazardous earthquake ground motions in many regions worldwide.…”
Section: S Eis MI C Ha Z Ard and A Sso Ciated Ris K Smentioning
confidence: 99%
“…We believe that PSHA is not "the natural phenomenon itself," and also, per "Cargo-cult statistics and scientific crisis" (Stark & Saltelli, 2018) that the underlying problem of a widespread pandemic-like scientific crisis in many disciplines collaboratively involved in SHA lies squarely in the misuse of Statistics far beyond the possibilities of its applications (as in the abovementioned GSHAP, STEP, GEM models) due to: (i) superficial education regarding "initial basic principles"; (ii) lots of mechanical application of available software and (iii) the questionable editorial policies of some scientific journals (see Bela & Panza, 2021;Stark, 2018;Stark & Saltelli, 2018).…”
Section: Predic Tionmentioning
confidence: 99%